Valuing Florida Water Resources: Summary by Regions - Fei He; Tatiana Borisova; Xiang Bi; Kelly Grogan (EDIS)
This article is a part of the EDIS series “Economic Value of Florida Water Resources” (see https://edis.ifas.ufl.edu/topic_series_valuing_florida_water_resources ). This series is aimed at helping water-resource professionals and interested citizens improve their knowledge of the economic value of goods and services provided by Florida water resources. The focus of this paper is specifically on supporting and regulating ecosystem services provided by Florida water resources.